2016
DOI: 10.5897/ajar2016.10947
|View full text |Cite
|
Sign up to set email alerts
|

The role of Crambe abyssinica in the control of Heterodera glycines (Thylenchida: Heteroidae)

Abstract: The soybean cyst nematode (SCN), Heterodera glycines, is present in more than 150 municipalities in Brazil, and the long persistence of the cysts in the soil combined with the severe degree of parasitism induces high soybean production losses. The objective of this study was to evaluate the biofumigant effect of Crambe abyssinica on the SCN population in the second soybean crop season. The experiment was conducted on a rural property whose soil was naturally infested with SCN. Crambe abyssinica was planted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies on crambe extracts have demonstrated its efficiency in controlling nematodes (Coltro-Roncato et al, 2016), whereas other studies incorporated crambe residues in soils colonized with nematodes (Nascimento, Jaime, G. E. Silva, A. R. Silva, & Alves, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on crambe extracts have demonstrated its efficiency in controlling nematodes (Coltro-Roncato et al, 2016), whereas other studies incorporated crambe residues in soils colonized with nematodes (Nascimento, Jaime, G. E. Silva, A. R. Silva, & Alves, 2016).…”
Section: Introductionmentioning
confidence: 99%